Operator Responsibilities in Safeguarding Consumer Rights Against GPS Spoofing in Ride-Hailing Services - Salvia, Hana; Priowirjanto, Enni Soerjati; Suwandono, Agus (PADJADJARAN JURNAL ILMU HUKUM (JOURNAL OF LAW), 2024)
This study examines the responsibilities of Electronic System Providers (ESPs) in safeguarding consumer rights within ride-hailing services. It specifically addresses the Global Positioning System (GPS) spoofing by drivers. The GPS spoofing involves the deceitful manipulation of location data by vehicles, posing significant legal and security risks to customers. The study evaluated the effectiveness of ESPs, including popular platforms in Indonesia like Gojek and Grab, in protecting consumers from such violations. It utilized normative legal theory and the secondary data analysis derived from ESP contracts. Findings indicate that current consumer protection measures are insufficient, primarily because ESPs employ exemption clauses that contravene Consumer Protection Law regulations. Additionally, the study highlights a lack of compliance with governance laws, such as the Government Regulation Number 71 of 2019, which mandates ESPs to establish robust and effective electronic system governance. This unethical practice jeopardizes consumer safety and erodes trust in the ESPs. This study underscores the necessity for stricter enforcement of consumer protection laws and regulations within the ride-hailing sector to ensure client safety and security. ESPs must prioritize safeguarding consumer data and implement measures to prevent drivers from manipulating fraudulent location data. Furthermore, collaborative efforts among ESPs, governmental bodies, and cybersecurity experts are essential to enhance legal protections for consumers, aiming to establish fair and safe procedures that benefit all parties involved.